Feed the Soil, Not the Plant: Case Studies in the Sustainability of Ontario’s Regional Orchestras - Chambers, Laura (MUSICultures, 2019)
Although Western Art Music (WAM) may not (yet!) be classified as a music-culture “at risk,” many of Ontario’s professional regional orchestras operate under increasingly unstable and difficult conditions. Using the theories of Jeff Todd Titon — whose evolving scholarship on the sustainability of musical cultures explores sustainability through a relational epistemology with the science of ecology — I examine the institutional health of two organizations within the WAM landscape of Ontario: The Niagara Symphony Orchestra and the ensemble previously known as Orchestra London.